The project method in the teaching-learning process of physics in pre-university education - Pacheco-Valencia, Dianelys (2023)
The research in the search for proposals that transform the teachinglearning process of Physics in pre-university education, had the objective of proposing a methodology that incorporates the project method in the teachinglearning process, to contribute to the development of motivation for the study of the subject Physics in the students and that they become the protagonists of their learning. For the development of the research, methods of collection and processing of the information gathered were used, within the latter, observation and survey stand out. The selected sample consisted of 196 students in the 10th grade of the “Capitan Roberto Rodríguez Fernández” Urban Pre-University Institute, located in the city of Santa Clara, Villa Clara, Cuba. The results obtained with the application of the methods showed that it is necessary to produce a transformation in the teaching-learning methods of Physics in the pre-university to stimulate the motivation for learning. Such results served as a basis to design and propose such methodology, which was submitted to experts’ criteria who evaluated it as pertinent. The results show the relevance of the Methodology for the Application of the Project Method.